Pengaruh Ancaman Siber dan Strategi Mitigasi Risiko terhadap Minat Menggunakan Layanan Mobile Banking BSI (Studi Kasus Mahasiswa FEBI UIN Sumatera Utara) - Siti Zuhairoh Ritonga; Nuri Aslami; Ahmad Perdana Indra (STIE Indonesia Banking School, 2026)
The advancement of digital technology prompts Islamic banking to enhance mobile banking services for improved transaction efficiency, while simultaneously increasing cyber dangers that may impact user engagement. “This study seeks to examine the impact of cyber threats and risk mitigation techniques on the inclination to utilize BSI mobile banking services among FEBI UIN North Sumatra students. The methodology employed is quantitative associative, utilizing a sample of 100 respondents chosen by purposive sampling methods. Data collection was executed via a Likert-scale questionnaire and analyzed through multiple linear regression utilizing SPSS version 25. The study's findings demonstrate that cyber threats exert a positive and significant impact on the inclination to utilize mobile banking, evidenced by a t value of 3.488 and a significance level of 0.001. Additionally, risk mitigation strategies also show a positive and significant effect, with a t value of 8.951 and a significance level of 0.000, marking them as the most influential variables. Collectively, these two variables affect interest in usage, with a coefficient of determination of 0.708, signifying that 70.8% of the variance in interest in mobile banking utilization can be accounted for by these variables. The findings of this study demonstrate that, despite the presence of cyber dangers, the application of effective risk mitigation techniques can enhance trust and stimulate interest in utilizing mobile banking services.